249 NECROTIZING ENTEROCOLITIS IN THE ERA OF INCREASING DONOR BREAST MILK USE IN PREMATURE INFANTS. Issue 1 (1st January 2007) - Bishop, C. E.; Blanco, C. L.; Burney, K.; Waite, L. L.; Petershack, J. A.
Abstract : Background: Necrotizing enterocolitis (NEC) is a significant cause of morbidity and mortality in very low birth weight (VLBW) infants. Previous studies have shown lower rates of NEC when preterm infants are fed their own mother's breast milk (MBM), but few studies have addressed the effects of donor breast milk (DBM). Objective: To describe the incidence of NEC as well as associated risk factors and morbidities in the era of increasing DBM use in VLBW infants. Design/Methods: Retrospective chart review of liveborn VLBW infants admitted to University Hospital, San Antonio, TX, from 2003 to 2004. One hundred ninety-one charts were reviewed; 40 were excluded due to previable status. NEC was defined according to Bell's criteria as stage II or higher. Only covariates of primary conceptual interest were included in the final multivariate model. Logistic regression, Fisher exact test, and multivariate analyses were performed using SPSS and SAS . Results: One hundred fifty-one patients were eligible for analysis. The mean gestational age (GA) and mean birth weight (BW) were 28.5 ± 2.9 weeks and 1, 061 ± 288 g, respectively. Eighty percent of infants were of Hispanic ethnicity and 55% were female. Seventy-eight percent of infants received primarily human milk by 336/7 weeks corrected GA; of these, 33% received primarily DBM. Fourteen patients developed NEC at a mean corrected GA of 30.8 ± 2.8 weeks. Lower GA was associated with NEC ( p = .05). After adjusting for GA, Apgar < 5, small for GA, and postnatal steroids, increased eosinophil counts were significantly associated with NEC ( p = .01), whereas type of human milk and fortification were not. A tendency toward a protective effect of erythropoietin use and a detrimental effect of additional enteral protein supplementation was observed. Infants with NEC had a significant increase in BPD (OR 5.3, CI 1.0-26) or death (OR 23, CI 2.4-219) but not IVH. Infants who developed NEC received significantly higher amounts of blood products (> 100 mL/kg) during their entire hospital stay (OR 5.6, CI 1.3-24). Conclusion: In our VLBW population, the incidence of NEC is consistent with rates previously reported. Infants who developed NEC were of younger GA and had higher eosinophil counts. Infants with NEC were more likely to die or develop BPD even after correction for other variables. In our preliminary data, the type of human milk had no significant correlation with NEC, although other known benefits of MBM were not evaluated due to sample size. Further studies of the use of donor breast milk are warranted.